Study on lateral friction resistance of concrete pouring structure in coral reef limestone formation - Zhang, Yongtao; Zhang, Ruiyuan; Chen, Peishuai; Ji, Fuquan; Luo, Huiwu; Liu, Enlong (Frontiers in Earth Science, 2024)
This study investigates the effects of interface shape and bonding conditions on the side friction resistance of the cast-in-place pile in coral reef limestone stratum of the China-Maldives Friendship Bridge area. Large-scale direct shear tests are performed on the coral reef limestone-concrete interface to investigate the exertion mechanism of interfacial strength. A finite-discrete element coupling method (FDEM) is employed to develop a constitutive model for coral reef limestone. A numerical calculation method for the side friction resistance capacity of pile foundations in coral reef limestone strata is proposed based on the bearing characteristics of side friction resistance in pile-coral reef limestone interactions. The shear tests on seven shapes of pile-rock interfaces indicate that bonding condition is the primary factor influencing interface strength, while interface shape has a minimal impact. The cement slurry fills the pores to form an interface reinforcement that possesses a strength greater than that of the coral reef limestone. The computational results from the constitutive model of coral reef limestone match well with the laboratory test results, demonstrating that the FDEM can effectively simulate the effects of high porosity and bonding strength on the mechanical properties of coral reef limestone. The FDEM-based numerical results for the interface strength between cast-in-place pile and coral reef limestone exhibit good consistency with the laboratory shear test results, which validates the effectiveness and accuracy of the numerical calculation method for side friction resistance of cast-in-place pile in coral reef limestone strata. These findings can provide valuable reference for the design and construction of pile foundations in marine island and reef projects.